Professional Reputation and Identity in the Online World - Kirwan, Gloria; Mc Guckin, Conor (My University, 2013)
The interface between new entrants to professional disciplines, professional reputation management and social media usage is an under-researched and little understood phenomenon. A small-scale study on social media usage conducted with new social workers and teachers, working in the Irish context, revealed interesting in-sights into the complexities of reputation management for new professionals and the particular issues related to development of their professional reputations raised by online interactions, relationships and behaviour. Key messages for professionals and professional educators emerge from the findings outlined in this article.
PUBLISHED
Keywords: Inclusive Society; Social Work; TEACHING; digital technology; professional ethics; Education; Social services, interventions and supports